SILINDER BERPENAMPANG AIRFOIL DARI PENJUMLAHAN DUA LINGKARAN - sihwaningrum, Idha (MATEMATIKA, 2002)
In two dimensional nonviscous incompressible irrotational fluid flow, the equipotential lines and the streamlines can be related to the real and imaginary part of the complex function respectively. By taking the streamlines equal to zero as the boundary fluid flows, we get several types of fluid flows such as fluid flow past a circular cylinder. Having addition of two cylinder in a certain position result in an airfoil, it it reseanoble for asking whether addition of two equation of fluid flow past a cylinder give an equation of fluid flow past an airfoil cylinder. This can be answer by examining a lift from the airfoil equation. It is difficult to obtain the actual value of the lift. To gain an understanding, we examine the change of square of the velocity in the neighbourhood of the airfoil. Bernoulli's equation provides the connection between the pressure and the square of the velocity . Then the knowledge of the square of the fluid flow velocity gives an indication of the pressure. Since the square of the fluid flow velocity in the neighbourhood below the airfoil is smaller than it is in the neighbourhood above the airfoil, then the pressure in the neighbourhood below the airfoil is greater than it is the neighbourhood above the airfoil. This indicates that we have a lift from the equation of fluid flow past an airfoil in which its equation formed by summing two equation of fluid flow past a cylinder.